Quality evaluation analysis method for copper-clad steel grounding material
By designing a quality evaluation and analysis method for copper-clad steel grounding materials based on indoor simulation acceleration test, the problem of time-consuming and costly evaluation of corrosion resistance performance of copper-clad steel grounding materials in the prior art is solved, and the rapid screening of qualified materials is achieved. The effect of reducing safety accidents and economic losses.
Patent Information
- Application Number
- CN202411355668.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-02-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, the corrosion resistance evaluation method of copper-clad steel grounding materials is time-consuming and costly, and it is difficult to quickly screen out qualified grounding materials, resulting in safety accidents and economic losses.
A method of quality evaluation and analysis of copper clad steel grounding material based on indoor simulation acceleration test was designed. By analyzing the corrosion of copper clad steel materials in an acidic environment, it detects whether the copper layer contains iron impurities, and passes optimized acid corrosion. The solution corrodes the material, measures the concentration of Cu2+ and Fe3+, draws its concentration-corrosion time change relationship curve, and evaluates the corrosion rate and corrosion resistance of the material.
This method can quickly detect the corrosion resistance of copper-covered steel grounding materials, screen out qualified grounding materials, reduce safety accidents and economic losses caused by corrosion, and improve the material selection and corrosion protection design efficiency of metal products.
Smart Images

Figure CN119413694A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper-clad steel materials, and in particular to a quality evaluation and analysis method for copper-clad steel grounding materials. Background Art
[0002] The grounding device is the cornerstone to ensure the normal operation of the power project, and it is also an important guarantee for maintaining the safety of power workers and electrical equipment. Correctly selecting and maintaining grounding materials, ensuring the safe operation of equipment, reducing the risk of electric shock, and improving system stability are important measures to ensure the safety of equipment and personnel. Grounding materials are an important component of grounding devices, usually made of metal materials with good electrical conductivity (such as copper, aluminum, etc.). These materials can effectively lead the current to the ground to protect the safety of equipment and personnel. When selecting grounding materials, it is necessary to consider their electrical conductivity, corrosion resistance and durability to ensure the stability and reliability of the grounding system. Copper has the characteristics of high electrical conductivity and good corrosion resistance, and is widely used as a grounding material. Pure copper is generally used as a grounding material abroad. However, the cost of copper is expensive, about ten times that of steel. In order to reduce costs, copper-clad steel is generally used as a grounding material. Copper-clad steel refers to a material in which the surface of an iron-carbon alloy body (steel matrix) is covered with copper. It has the excellent conductivity and corrosion resistance of the copper layer, as well as the high strength, high thermal resistance and high magnetic permeability of the iron-carbon alloy, so it can be used as a grounding material.
[0003] For copper-clad steel grounding materials, the integrity of the copper plating on its surface determines the service life of the grounding material. If the copper plating on the surface is damaged and the steel is exposed, the stability of the grounding material will be greatly reduced and it will be easy to corrode, thus shortening its service life. In the current environment, metal corrosion mainly includes two types: chemical corrosion and electrochemical corrosion. Chemical corrosion refers to the process in which metal and medium directly react chemically to form compounds. For example, the reaction of copper on the outer layer of copper-clad steel with oxygen to form copper oxide is chemical corrosion. Direct chemical reaction between metal and oxidizing or highly active substances will cause surface damage. Electrochemical corrosion is caused by the potential difference between metals, forming a primary cell in the presence of an electrolyte, causing local corrosion of the metal. Generally, when impure metals come into contact with electrolyte solutions, a primary cell reaction will occur, in which the more active metal loses electrons and is oxidized. The difference between chemical corrosion and electrochemical corrosion lies in whether an electric current is generated.
[0004] The outer copper of the copper-clad steel material will chemically corrode to form an oxide layer, which still has a certain protective effect on the inner steel substrate. However, once the outer copper layer breaks, the inner steel substrate will be exposed. Due to the potential difference between the copper layer and the steel substrate (iron-carbon alloy), the iron in the steel substrate is more active than copper and is more likely to lose electrons. In the soil environment, there is an electrolyte, and a galvanic cell will be formed between the copper layer and the steel substrate, causing electrochemical corrosion. The rate of electrochemical corrosion is much higher than that of chemical corrosion, which will significantly accelerate the overall corrosion rate of the material. In addition, the copper layer of the copper-clad steel material usually contains iron impurities, which will also affect the corrosion resistance of the copper-clad steel material.
[0005] At present, the main evaluation method for the corrosion resistance of copper-clad steel is the on-site buried test. The on-site buried test is a corrosion test method conducted in an actual soil environment, that is, burying the metal sample in the soil for a period of time to observe its corrosion in the soil in order to evaluate the corrosion resistance of the metal under actual use conditions. However, this method has a long test cycle and requires a lot of manpower and material resources.
[0006] Indoor simulated accelerated test refers to a test method that simulates outdoor natural environmental conditions by controlling the proportion of chemicals in the laboratory based on the important parameters that affect metal corrosion. Indoor simulated accelerated corrosion can simulate the natural corrosion environment while accelerating the corrosion rate. It can determine the tendency of metal materials to undergo certain corrosion, the relative corrosion resistance of materials, or the strength of medium erosion in a relatively short period of time.
[0007] Therefore, it is necessary to design a quality evaluation and analysis method for copper-clad steel grounding materials based on indoor simulation accelerated tests. Summary of the invention
[0008] The purpose of the present invention is to solve at least one of the technical problems existing in the prior art and to provide a quality evaluation and analysis method for a copper-clad steel grounding material.
[0009] To achieve the above object, the technical solution adopted by the present invention is as follows: A quality evaluation and analysis method for copper-clad steel grounding materials, comprising the following steps:
[0010] Step 1, by analyzing the corrosion condition of the copper-clad steel grounding material when used in an acidic environment, preliminarily selecting an acidic corrosion solution that can corrode the copper-clad steel grounding material;
[0011] Step 2, by detecting whether the copper layer of the copper-clad steel grounding material contains iron impurities, analyzing the material of the copper layer of the copper-clad steel grounding material, and detecting and analyzing that the copper layer of the copper-clad steel grounding material contains iron impurities;
[0012] Step 3, based on the copper layer of the copper-clad steel grounding material including a copper main body and iron impurities, a first acidic corrosive solution is selected to corrode the copper main body, and a second acidic corrosive solution is selected to corrode the iron impurities, and the formulas of the first acidic corrosive solution and the second acidic corrosive solution are optimized;
[0013] Step 4, the copper-clad steel grounding material containing iron impurities is corroded by using the optimized first acidic corrosion solution and the second acidic corrosion solution, and the corrosion products containing Cu 2+ and Fe 3+ ;
[0014] Step 5, using UV-visible spectrophotometry to test the Cu in the first acidic corrosion solution 2+ Concentration and Fe in the second acidic corrosive solution 3+ The concentration of Cu 2+ and Fe 3+ Concentration-corrosion time variation curve;
[0015] Step 6, according to Cu 2+ The concentration-corrosion time variation curve of Cu 2+ The slope of the curve and define Cu 2+ The slope of the curve is the corrosion rate of the copper-clad steel grounding material. The faster the corrosion rate of the copper-clad steel grounding material, the worse the corrosion resistance. 3+ The concentration-corrosion time variation curve of Fe 3+ The slope of the curve, observe Fe 3+ The slope of the curve and Cu 2+ The correlation of the slope of the curve is used to analyze the influence of iron impurities on the corrosion resistance of copper-clad steel grounding materials.
[0016] Furthermore, in step 1, it specifically includes: according to the analysis that the copper layer of the copper-clad steel grounding material will dissolve in an oxidizing acidic environment, an acidic corrosion solution based on the oxidant Na2S2O8 is initially selected to corrode the copper layer.
[0017] Furthermore, in step 2, it specifically includes:
[0018] The detection of iron impurities in copper layer is based on Fe 3+ This is achieved by a color reaction with Ssal;
[0019] That is, drop an acidic corrosive solution containing Ssal onto the sample surface of the copper-clad steel grounding material, and observe whether the drop changes color; if it turns purple-red, it means that the copper layer of the copper-clad steel contains Fe impurities.
[0020] Furthermore, in step 3, it specifically includes:
[0021] The first acidic etching solution is a H2SO4-based acidic etching solution, which is used to corrode the copper body; the components of the H2SO4-based acidic etching solution include 80g of Na2S2O8 and 10μL of H2SO4, and the components of the H2SO4-based acidic etching solution are dissolved in 400mL of deionized water, and the pH of the solution is adjusted by adding NaAc, and the pH range of the H2SO4-based acidic etching solution is 2 to 7;
[0022] The second acidic corrosion solution is a Ssal-based acidic corrosion solution, which is used to corrode iron impurities; the components of the Ssal-based acidic corrosion solution include 80g of Na2S2O8 and 0.05g of Ssal. The components of the Ssal-based acidic corrosion solution are dissolved in 400mL of deionized water, and the pH of the solution is adjusted by adding NaAc. The pH range of the Ssal-based acidic corrosion solution is 2 to 7.
[0023] Furthermore, in step 3, it specifically includes:
[0024] A 60mm×20mm×1mm copper sheet was used as the research object to study the effects of the oxidant concentration and pH of the acidic corrosion solution on the corrosion rate of the copper sheet in order to optimize the formula of the acidic corrosion solution.
[0025] The corrosion rate of the copper sheet was evaluated by the weighing method. Specifically, during the corrosion process, the sample was taken out from the corrosion solution every 15 minutes, the residual solution on the surface was rinsed with deionized water, and the sample was quickly weighed after being dried with filter paper. The relationship between the mass of the copper sheet and the corrosion time was plotted with the sample mass as the ordinate and the corrosion time as the abscissa.
[0026] According to the curve of the relationship between the mass of the copper sheet and the corrosion time, it can be concluded that when the pH of the corrosion solution is 7, the mass of the copper sheet does not change; when the initial pH of the corrosion solution is in the range of 2 to 6, as the corrosion reaction proceeds, the final pH of the corrosion solution approaches 2.7;
[0027] It was screened out that in the formula of the optimized acidic corrosion solution, the concentration of the oxidant Na2S2O8 was 0.84 mol / L, and the copper-clad steel grounding material was corroded under the condition of an initial pH of 3.
[0028] Furthermore, in step 5, it specifically includes:
[0029] Fe in the corrosion solution 3+ The concentration was tested by measuring the absorbance of the Fe-Ssal complex spectrophotometrically;
[0030] The maximum absorption wavelength position of the Fe-Ssal complex was determined. In a solution with a pH of 1 to 3, a 1:1 complex [Fe(Ssal)] was formed, the solution was purple-red, and the maximum absorption wavelength was 497nm; in a solution with a pH of 4 to 7, a 2:1 complex [Fe(Ssal)2] was formed, the solution was brown, and the maximum absorption wavelength was 468nm.
[0031] Therefore, the absorbance of [Fe(Ssal)] was tested in the pH range of 1 to 3 by UV-visible spectrophotometry to test the Fe in the corrosion solution. 3+ concentration, thus plotting Fe 3+ Concentration-corrosion time variation curve.
[0032] Furthermore, in step 5, it specifically includes:
[0033] Cu 2+ In acidic solution, it appears as blue hydrated ion Cu(H2O)4 2+ exists in the form of;
[0034] The corrosion rate of copper was evaluated by UV-visible spectrophotometry, which measures the absorption peak intensity of the corrosion solution at a wavelength of 810 nm to measure the Cu(H2O)4 2+ The concentration changes, thus plotting the Cu 2+ Concentration-corrosion time variation curve.
[0035] Furthermore, in step 6, it specifically includes:
[0036] It was observed that when Fe 3+ The greater the slope of the curve, the Cu 2+ The greater the slope of the curve, the more negative the presence of iron impurities has on the corrosion resistance of the copper-clad steel grounding material.
[0037] Comparative corrosion tests of copper rods and copper-clad steel samples were conducted to verify that the presence of iron impurities had a negative impact on the corrosion resistance of copper-clad steel grounding materials.
[0038] Further, in step 6, the corrosion comparison test of the copper rod and the copper-clad steel sample specifically includes:
[0039] The comparative test selected commercially available T1 grade copper rods and copper-clad steel samples, used acidic corrosion solution to corrode the copper rods and copper-clad steel samples respectively, and used an online spectrophotometer to test the corrosion rate;
[0040] The corrosion results of the copper rod and copper-clad steel samples in the second acidic corrosion solution show that the solution of the copper-clad steel sample after corrosion is brown-red, indicating that the copper layer of the copper-clad steel sample contains Fe impurities; while the solution of the copper rod after corrosion is not brown-red, indicating that the copper rod does not contain Fe impurities;
[0041] The corrosion results of copper rods and copper-clad steel samples in the first acidic corrosion solution showed that within the same corrosion time, the corrosion rate of the copper-clad steel samples was greater than that of the copper rods, verifying that the presence of iron impurities had a negative impact on the corrosion resistance of the copper-clad steel grounding material.
[0042] It can be seen from the above description of the present invention that, compared with the prior art, the quality evaluation and analysis method of the copper-clad steel grounding material of the present invention includes at least one of the following beneficial effects:
[0043] 1. The quality evaluation and analysis method of the copper-clad steel grounding material of the present invention can quickly detect the corrosion resistance of the copper-clad steel grounding material, screen out qualified grounding materials, and reduce safety accidents and economic losses caused by corrosion, which is of great significance to economy and safety;
[0044] 2. The quality evaluation and analysis method of the copper-clad steel grounding material of the present invention can quickly evaluate the corrosion resistance of metal materials produced by different manufacturers by analyzing the corrosion mechanism of the copper-clad steel grounding material, thereby improving the material selection and anti-corrosion design efficiency of metal products;
[0045] 3. The quality evaluation and analysis method of the copper-clad steel grounding material of the present invention can more comprehensively evaluate the corrosion resistance of materials such as copper-clad steel, and provide more accurate and reliable data support for the research, development and application of materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 The present invention is a flowchart of the steps of a quality evaluation and analysis method of a copper-clad steel grounding material in a preferred embodiment of the present invention. DETAILED DESCRIPTION
[0047] The technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. Based on the embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0048] Reference Figure 1 As shown, a preferred embodiment of the present invention is a quality evaluation and analysis method for copper-clad steel grounding materials, comprising the following steps:
[0049] Step 1, by analyzing the corrosion condition of the copper-clad steel grounding material when used in an acidic environment, preliminarily selecting an acidic corrosion solution that can corrode the copper-clad steel grounding material;
[0050] Step 2, by detecting whether the copper layer of the copper-clad steel grounding material contains iron impurities, analyzing the material of the copper layer of the copper-clad steel grounding material, and detecting and analyzing that the copper layer of the copper-clad steel grounding material contains iron impurities;
[0051] Step 3, based on the copper layer of the copper-clad steel grounding material including a copper main body and iron impurities, a first acidic corrosive solution is selected to corrode the copper main body, and a second acidic corrosive solution is selected to corrode the iron impurities, and the formulas of the first acidic corrosive solution and the second acidic corrosive solution are optimized;
[0052] Step 4, the copper-clad steel grounding material containing iron impurities is corroded by using the optimized first acidic corrosion solution and the second acidic corrosion solution, and the corrosion products containing Cu 2+ and Fe 3+ ;
[0053] Step 5, using UV-visible spectrophotometry to test the Cu in the first acidic corrosion solution 2+ Concentration and Fe in the second acidic corrosive solution 3+ The concentration of Cu 2+ and Fe 3+ Concentration-corrosion time variation curve;
[0054] Step 6, according to Cu 2+ The concentration-corrosion time variation curve of Cu 2+ The slope of the curve and define Cu 2+ The slope of the curve is the corrosion rate of the copper-clad steel grounding material. The faster the corrosion rate of the copper-clad steel grounding material, the worse the corrosion resistance. 3+ The concentration-corrosion time variation curve of Fe 3+ The slope of the curve, observe Fe 3+ The slope of the curve and Cu 2+ The correlation of the slope of the curve is used to analyze the influence of iron impurities on the corrosion resistance of copper-clad steel grounding materials.
[0055] The quality evaluation and analysis method of the copper-clad steel grounding material of the present invention can quickly detect the corrosion resistance of the copper-clad steel grounding material, screen out qualified grounding materials, and reduce safety accidents and economic losses caused by corrosion, which is of great significance to economy and safety; the quality evaluation and analysis method of the copper-clad steel grounding material of the present invention can quickly evaluate the corrosion resistance of metal materials produced by different manufacturers by analyzing the corrosion mechanism of the copper-clad steel grounding material, and improve the material selection and anti-corrosion design efficiency of metal products; the quality evaluation and analysis method of the copper-clad steel grounding material of the present invention can more comprehensively evaluate the corrosion resistance of materials such as copper-clad steel, and provide more accurate and reliable data support for the research, development and application of materials.
[0056] As a preferred embodiment of the present invention, it may also have the following additional technical features:
[0057] In this embodiment, in step 1, specifically including: according to the analysis that the copper layer of the copper-clad steel grounding material will dissolve in an oxidizing acidic environment, an acidic corrosion solution based on the oxidant Na2S2O8 is initially selected to corrode the copper layer.
[0058] Copper has a higher electrode potential than hydrogen and is a metal with a relatively positive potential. Copper will not replace hydrogen in an acidic environment and is almost uncorroded in non-oxidizing acids and acid solutions that are not filled with air or oxygen. Copper will dissolve in an oxidizing acidic environment.
[0059] In this embodiment, step 2 specifically includes:
[0060] The detection of iron impurities in copper layer is based on Fe 3+ It is achieved by a color reaction with Ssal, wherein Ssal is sulfosalicylic acid;
[0061] That is, drop an acidic corrosive solution containing Ssal onto the sample surface of the copper-clad steel grounding material, and observe whether the drop changes color; if it turns purple-red, it means that the copper layer of the copper-clad steel contains Fe impurities.
[0062] In this embodiment, step 3 specifically includes:
[0063] The first acidic corrosion solution is a H2SO4-based acidic corrosion solution, which is used to corrode the copper body; the components of the H2SO4-based acidic corrosion solution include 80g of Na2S2O8 and 10μL of H2SO4, and the components of the H2SO4-based acidic corrosion solution are dissolved in 400mL of deionized water, and the pH of the solution is adjusted by adding NaAc, and the pH range of the H2SO4-based acidic corrosion solution is 2 to 7; the specific formula is shown in Table 1:
[0064] Table 1 Composition of H2SO4-based acidic corrosion solutions under different pH conditions
[0065]
[0066] The second acidic corrosion solution is a Ssal-based acidic corrosion solution, which is used to corrode iron impurities; the components of the Ssal-based acidic corrosion solution include 80g of Na2S2O8 and 0.05g of Ssal, and the components of the Ssal-based acidic corrosion solution are dissolved in 400mL of deionized water, and the pH of the solution is adjusted by adding NaAc, and the pH range of the Ssal-based acidic corrosion solution is 2 to 7; the specific formula is shown in Table 2:
[0067] Table 2 Composition of Ssal-based acidic corrosion solutions under different pH conditions
[0068]
[0069] In this embodiment, step 3 specifically includes:
[0070] A 60mm×20mm×1mm copper sheet was used as the research object to study the effects of the oxidant concentration and pH of the acidic corrosion solution on the corrosion rate of the copper sheet in order to optimize the formula of the acidic corrosion solution.
[0071] The corrosion rate of the copper sheet was evaluated by the weighing method. Specifically, during the corrosion process, the sample was taken out from the corrosion solution every 15 minutes, the residual solution on the surface was rinsed with deionized water, and the sample was quickly weighed after being dried with filter paper. The relationship between the mass of the copper sheet and the corrosion time was plotted with the sample mass as the ordinate and the corrosion time as the abscissa.
[0072] According to the curve of the relationship between the mass of the copper sheet and the corrosion time, it can be concluded that when the pH of the corrosion solution is 7, the mass of the copper sheet does not change; when the initial pH of the corrosion solution is in the range of 2 to 6, as the corrosion reaction proceeds, the final pH of the corrosion solution approaches 2.7;
[0073] It was screened out that in the formula of the optimized acidic corrosion solution, the concentration of the oxidant Na2S2O8 was 0.84 mol / L, and the copper-clad steel grounding material was corroded under the condition of an initial pH of 3.
[0074] In this embodiment, step 5 specifically includes:
[0075] Fe in the corrosion solution 3+ The concentration was tested by measuring the absorbance of the Fe-Ssal complex spectrophotometrically;
[0076] The maximum absorption wavelength position of the Fe-Ssal complex was determined. In a solution with a pH of 1 to 3, a 1:1 complex [Fe(Ssal)] was formed, the solution was purple-red, and the maximum absorption wavelength was 497nm; in a solution with a pH of 4 to 7, a 2:1 complex [Fe(Ssal)2] was formed, the solution was brown, and the maximum absorption wavelength was 468nm.
[0077] Therefore, the absorbance of [Fe(Ssal)] was tested in the pH range of 1 to 3 by UV-visible spectrophotometry to test the Fe in the corrosion solution. 3+ concentration, thus plotting Fe 3+ Concentration-corrosion time variation curve.
[0078] In this embodiment, step 5 specifically includes:
[0079] Cu 2+In acidic solution, it appears as blue hydrated ion Cu(H2O)4 2+ exists in the form of;
[0080] The corrosion rate of copper was evaluated by UV-visible spectrophotometry, which measures the absorption peak intensity of the corrosion solution at a wavelength of 810 nm to measure the Cu(H2O)4 2+ The concentration changes, thus plotting the Cu 2+ Concentration-corrosion time variation curve.
[0081] In this embodiment, step 6 specifically includes:
[0082] It was observed that when Fe 3+ The greater the slope of the curve, the Cu 2+ The greater the slope of the curve, the more negative the presence of iron impurities has on the corrosion resistance of the copper-clad steel grounding material.
[0083] Comparative corrosion tests of copper rods and copper-clad steel samples were conducted to verify that the presence of iron impurities had a negative impact on the corrosion resistance of copper-clad steel grounding materials.
[0084] In this embodiment, in step 6, the corrosion comparison test of the copper rod and the copper-clad steel sample specifically includes:
[0085] The comparative test selected commercially available T1 grade copper rods and copper-clad steel samples, used acidic corrosion solution to corrode the copper rods and copper-clad steel samples respectively, and used an online spectrophotometer to test the corrosion rate;
[0086] The corrosion results of the copper rod and copper-clad steel samples in the second acidic corrosion solution show that the solution of the copper-clad steel sample after corrosion is brown-red, indicating that the copper layer of the copper-clad steel sample contains Fe impurities; while the solution of the copper rod after corrosion is not brown-red, indicating that the copper rod does not contain Fe impurities;
[0087] The corrosion results of copper rods and copper-clad steel samples in the first acidic corrosion solution showed that within the same corrosion time, the corrosion rate of the copper-clad steel samples was greater than that of the copper rods, verifying that the presence of iron impurities had a negative impact on the corrosion resistance of the copper-clad steel grounding material.
[0088] More specifically, the comparative test showed that the corrosion curve slope k1 of the copper-clad steel sample was 0.02237, while the corrosion curve slope k2 of the copper rod was 0.01305; therefore, the comparative results showed that the corrosion rate of the copper-clad steel sample was 1.71 times that of the copper rod.
[0089] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and improved concepts of the present invention within the technical scope disclosed by the present invention, and they should be covered by the protection scope of the present invention.
Claims
1. A quality evaluation and analysis method for copper-clad steel grounding materials, characterized in that: The following steps are involved: Step 1, by analyzing the corrosion condition of the copper-clad steel grounding material when used in an acidic environment, preliminarily selecting an acidic corrosion solution that can corrode the copper-clad steel grounding material; Step 2, by detecting whether the copper layer of the copper-clad steel grounding material contains iron impurities, analyzing the material of the copper layer of the copper-clad steel grounding material, and detecting and analyzing that the copper layer of the copper-clad steel grounding material contains iron impurities; Step 3, based on the copper layer of the copper-clad steel grounding material including a copper main body and iron impurities, a first acidic corrosive solution is selected to corrode the copper main body, and a second acidic corrosive solution is selected to corrode the iron impurities, and the formulas of the first acidic corrosive solution and the second acidic corrosive solution are optimized; Step 4, the copper-clad steel grounding material containing iron impurities is corroded by using the optimized first acidic corrosion solution and the second acidic corrosion solution, and the corrosion products containing Cu 2+ and Fe 3+ ; Step 5, using UV-visible spectrophotometry to test the Cu in the first acidic corrosion solution 2+ Concentration and Fe in the second acidic corrosive solution 3+ The concentration of Cu 2+ and Fe 3+ Concentration-corrosion time variation curve; Step 6, according to Cu 2+ The concentration-corrosion time variation curve of Cu 2+ The slope of the curve and define Cu 2+ The slope of the curve is the corrosion rate of the copper-clad steel grounding material. The faster the corrosion rate of the copper-clad steel grounding material, the worse the corrosion resistance. 3+ The concentration-corrosion time variation curve is used to find Fe 3+ The slope of the curve, observe Fe 3+ The slope of the curve is related to Cu 2+ The correlation of the slope of the curve is used to analyze the influence of iron impurities on the corrosion resistance of copper-clad steel grounding materials.
2. The quality evaluation and analysis method of a copper-clad steel grounding material according to claim 1 is characterized in that: In step 1, specifically, it includes: according to the analysis that the copper layer of the copper-clad steel grounding material will dissolve in an oxidizing acidic environment, an acidic corrosion solution based on the oxidant Na2S2O8 is initially selected to corrode the copper layer.
3. The quality evaluation and analysis method of a copper-clad steel grounding material according to claim 1 is characterized in that: In step 2, specifically including: The detection of iron impurities in copper layer is based on Fe 3+ This is achieved by a color reaction with Ssal; That is, drop an acidic corrosive solution containing Ssal onto the sample surface of the copper-clad steel grounding material, and observe whether the drop changes color; if it turns purple-red, it means that the copper layer of the copper-clad steel contains Fe impurities.
4. The quality evaluation and analysis method of a copper-clad steel grounding material according to claim 1 is characterized in that: In step 3, it specifically includes: The first acidic etching solution is a H2SO4-based acidic etching solution, which is used to corrode the copper body; the components of the H2SO4-based acidic etching solution include 80g of Na2S2O8 and 10μL of H2SO4, and the components of the H2SO4-based acidic etching solution are dissolved in 400mL of deionized water, and the pH of the solution is adjusted by adding NaAc, and the pH range of the H2SO4-based acidic etching solution is 2 to 7; The second acidic corrosion solution is a Ssal-based acidic corrosion solution, which is used to corrode iron impurities; the components of the Ssal-based acidic corrosion solution include 80g of Na2S2O8 and 0.05g of Ssal. The components of the Ssal-based acidic corrosion solution are dissolved in 400mL of deionized water, and the pH of the solution is adjusted by adding NaAc. The pH range of the Ssal-based acidic corrosion solution is 2 to 7.
5. The quality evaluation and analysis method of a copper-clad steel grounding material according to claim 4 is characterized in that: In step 3, it specifically includes: A 60mm×20mm×1mm copper sheet was used as the research object to study the effects of the oxidant concentration and pH of the acidic corrosion solution on the corrosion rate of the copper sheet in order to optimize the formula of the acidic corrosion solution. The corrosion rate of the copper sheet was evaluated by the weighing method. Specifically, during the corrosion process, the sample was taken out from the corrosion solution every 15 minutes, the residual solution on the surface was rinsed with deionized water, and the sample was quickly weighed after being dried with filter paper. The relationship between the mass of the copper sheet and the corrosion time was plotted with the sample mass as the ordinate and the corrosion time as the abscissa. According to the curve of the relationship between the mass of the copper sheet and the corrosion time, it can be concluded that when the pH of the corrosion solution is 7, the mass of the copper sheet does not change; when the initial pH of the corrosion solution is in the range of 2 to 6, as the corrosion reaction proceeds, the final pH of the corrosion solution approaches 2.7; It was screened out that in the formula of the optimized acidic corrosion solution, the concentration of the oxidant Na2S2O8 was 0.84 mol / L, and the copper-clad steel grounding material was corroded under the condition of an initial pH of 3.
6. The quality evaluation and analysis method of a copper-clad steel grounding material according to claim 1 is characterized in that: In step 5, it specifically includes: Fe in the corrosion solution 3+ The concentration was tested by measuring the absorbance of the Fe-Ssal complex spectrophotometrically; The maximum absorption wavelength position of the Fe-Ssal complex was determined. In a solution with a pH of 1 to 3, a 1:1 complex [Fe(Ssal)] was formed, the solution was purple-red, and the maximum absorption wavelength was 497nm; in a solution with a pH of 4 to 7, a 2:1 complex [Fe(Ssal)2] was formed, the solution was brown, and the maximum absorption wavelength was 468nm. Therefore, the absorbance of [Fe(Ssal)] was tested in the pH range of 1 to 3 by UV-visible spectrophotometry to test the Fe in the corrosion solution. 3+ concentration, thus plotting Fe 3+ Concentration-corrosion time variation curve.
7. The quality evaluation and analysis method of a copper-clad steel grounding material according to claim 1 is characterized in that: In step 5, it specifically includes: Cu 2+ In acidic solution, it appears as blue hydrated ion Cu(H2O)4 2+ exists in the form of; The corrosion rate of copper was evaluated by UV-visible spectrophotometry, which measures the absorption peak intensity of the corrosion solution at a wavelength of 810 nm to measure the Cu(H2O)4 2+ The concentration changes, thus plotting the Cu 2+ Concentration-corrosion time variation curve.
8. The quality evaluation and analysis method of a copper-clad steel grounding material according to claim 1 is characterized in that: In step 6, specifically including: It was observed that when Fe 3+ The larger the slope of the curve, the higher the Cu 2+ The greater the slope of the curve, the more negative the presence of iron impurities has on the corrosion resistance of the copper-clad steel grounding material. Comparative corrosion tests of copper rods and copper-clad steel samples were conducted to verify that the presence of iron impurities had a negative impact on the corrosion resistance of copper-clad steel grounding materials.
9. The quality evaluation and analysis method of a copper-clad steel grounding material according to claim 1 is characterized in that: In step 6, the corrosion comparison test of the copper rod and the copper-clad steel sample specifically includes: The comparative test selected commercially available T1 grade copper rods and copper-clad steel samples, used acidic corrosion solution to corrode the copper rods and copper-clad steel samples respectively, and used an online spectrophotometer to test the corrosion rate; The corrosion results of the copper rod and copper-clad steel samples in the second acidic corrosion solution show that the solution of the copper-clad steel sample after corrosion is brown-red, indicating that the copper layer of the copper-clad steel sample contains Fe impurities; while the solution of the copper rod after corrosion is not brown-red, indicating that the copper rod does not contain Fe impurities; The corrosion results of copper rods and copper-clad steel samples in the first acidic corrosion solution showed that within the same corrosion time, the corrosion rate of the copper-clad steel samples was greater than that of the copper rods, verifying that the presence of iron impurities had a negative impact on the corrosion resistance of the copper-clad steel grounding material.
Citation Information
Patent Citations
Method for rapidly evaluating protective performance of galvanized steel coating through visual colorimetric method
CN115876680A
Device and method for detecting corrosion resistance of galvanized steel
CN116735465A
Indicator for detecting failure of copper-clad layer of copper-clad steel as well as preparation method and application of indicator
CN117347353A